THE TEACHING OF EFL READING IN THE INDONESIAN CONTEXT: THE STATE OF THE ART - Bambang Yudi Cahyono (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
Abstract: Skills in reading (and learning information from) texts written in English as a foreign language (EFL reading) constitute an important element of the establishment of English curriculum of secondary and tertiary schools (both English and non-English departments) in Indonesia. The need of the learners to be skilled in reading to learn has inspired EFL reading teachers or specialists to apply some techniques in the teaching of EFL reading and to investigate the effects of the techniques on improving Indonesian studentsÃ¢â¬â¢ reading skills, as well as to examine various related aspects such as reading materials, reading strategies, and factors affecting reading comprehension. Our purpose in writing this article is to review recent development in the EFL reading pedagogy and research in Indonesia and to view it from the broader perspective on the theories of reading processÃÂ and ESL/EFL reading instruction. Drawing on the results of this analysis, we will outline the current trends and recommend future direction in the EFL reading pedagogy and research in this country.